Triggered by Defeat or Victory? Assessing the Impact of Presidential Election Results on Extreme Right-Wing Mobilization Online. Issue 5 (4th May 2021) - Scrivens, Ryan; Burruss, George W.; Holt, Thomas J.; Chermak, Steven M.; Freilich, Joshua D.; Frank, Richard
ABSTRACT: The theoretical literature from criminology, social movements, and political sociology, among others, includes diverging views about how political outcomes could affect movements. Many theories argue that political defeats motivate the losing side to increase their mobilization while other established models claim the winning side may feel encouraged and thus increase their mobilization. We examine these diverging perspectives in the context of the extreme right online and recent presidential elections by measuring the effect of the 2008 and 2016 election victories of Obama and Trump on the volume of postings on the largest white supremacy web-forum. ARIMA time series using intervention modeling showed a significant and sizable increase in the total number of posts and right-wing extremist posts but no significant change for firearm posts in either election year. However, the volume of postings for all impact measures was highest for the 2008 election.